RELEVANSI KRITIK SANAD HADITS TARBAWI TERHADAP PENYEBARAN HADITS VIRAL DI MEDIA SOSIAL - Magfira, Nurul; Suwandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid growth of social media has transformed the dissemination of Islamic teachings, including tarbawi hadiths related to education, morality, and character building. Platforms such as TikTok, Instagram, YouTube, and WhatsApp have become major channels for spreading religious content. However, many hadiths circulating on social media are shared without sanad verification, potentially leading to the spread of weak or unauthentic hadiths. This study aims to analyze the relevance of sanad criticism in responding to the phenomenon of viral tarbawi hadiths on social media. This research employed a qualitative approach using library research methods. Data were collected from digital da’wah content, scholarly journals, and literature related to hadith studies and sanad criticism, particularly from the perspective of Muhammad Mustafa al-Azami. The findings reveal that several viral tarbawi hadiths on social media lack clear sanad validity and are often disseminated without reliable references. Sanad criticism remains relevant as a scientific method for verifying hadith authenticity in the digital era while also strengthening digital religious literacy and encouraging critical attitudes toward religious information on social media.